Significance Of Extracurricular Activities In Overall Development And Enhancement In Employability Of A Student - GagandeepBhullar,; Singh, DrSatinderpal (The journal of contemporary issues in business and government, 2021)
The paper highlights the significance of Extracurricular Activities in the overall development of the student and enhancing their employability. Using database like Google scholar, JSTOR, Web of Science total 63 papers were reviewed which became a sufficient primary source.The chosen references were taken from articles, review of literature, dissertations, conference proceedings, etc.